2017
DOI: 10.1002/mnfr.201600558
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet–gene interactions: A targeted metabolomics study in Greek‐Cypriot women

Abstract: Serum levels of flavin mononucleotide and 5-MTHF were shown to be influenced by interactions between GSTM1 deletion or MTHFR (rs1801133) polymorphisms and a dietary pattern, characteristic of MD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Since the whole body participates in the metabolic process and each cell releases its own metabolites, many factors can influence the results of metabolomics raw data29 such as, gender,30 drug usage3 and dietary habits.31 African-American or Caucasian women have shown different metabolic profiles of triple-negative breast cancer (TNBC) 32. These differences suggest that racial differences may alter the metabolites of BC.…”
Section: Factors Influencing Metabolomics Raw Datamentioning
confidence: 99%
“…Since the whole body participates in the metabolic process and each cell releases its own metabolites, many factors can influence the results of metabolomics raw data29 such as, gender,30 drug usage3 and dietary habits.31 African-American or Caucasian women have shown different metabolic profiles of triple-negative breast cancer (TNBC) 32. These differences suggest that racial differences may alter the metabolites of BC.…”
Section: Factors Influencing Metabolomics Raw Datamentioning
confidence: 99%
“…That has motivated lots of studies focusing on the potential link between the nutrients associated with onecarbon metabolism pathway and carcinogenesis (Milne, et al 2017, Weinstein, et al 2006. A previous study showed that SNPs of one-carbon metabolism gene have interactions with folate intake to affect the BC risk (Kakkoura, et al 2017). However, most previous studies focus on the effect of individual nutrients rather than a combination of foods (Lissowska, et al 2007), which have been limited in interpreting the high degree of intercorrelation among various nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…This has motivated lots of studies focusing on the potential associations between the nutrients associated with one-carbon metabolism pathway and carcinogenesis (Milne, et al 2017, Weinstein, et al 2006. As previous studies showed, some SNPs of one-carbon metabolism gene have interactions with folate intake to affect the BC risk (Kakkoura, et al 2017). However, the majority of the previous studies focus on the effect of individual nutrients rather than a combination of foods (Lissowska, et al 2007), which have been limited in interpreting the high degree of intercorrelation among various nutrients.…”
Section: Discussionmentioning
confidence: 99%